Restoration of functional capabilities of persons of early adult age with TBI, obtained as a result of combat actions means by physical therapy - Kozova, N.; Boshak, Y.; Hymon, V.; Tymoshenko, Y. (Actual Problems of Medicine and Pharmacy, 2021)
In the presented master's work the general theoretical and practical aspects of restoration of functional capabilities of young adults with TBI received as a result of hostilities are revealed. The modern means and methods of physical therapy at the given nosology are analyzed, algorithms of actions of process of physical therapy are considered, the program of physical therapy for persons with TBI received as a result of military operations is substantiated. Proved that physical therapy has been shown to increase muscle strength, reduce spasticity, improve coordination and balance, and thus improve quality of life and reduce the patient's limited life.